HUBUNGAN KOMUNIKASI ORGANISASI DENGAN KEPUASAN KERJA PEGAWAI DI DINAS PENDIDIKAN KOTA SAWAHLUNTO - Dahliawati (Jurnal Bahana Manajemen Pendidikan, 2015)
This research aimed to describe the organizational communications, employee job satisfaction, and correlational organizational communications with employee job satisfaction in department of education Sawahlunto. The population is 69 employee and the sample is 61 employee. Instrumen that used questionnaire scale likert model . The techhique of data analysis is done by using formula Product Moment Correlation and T-test. The result of the data analysis showed that (1) organizational communication at department of education Sawahlunto is good at 84,6%, (2) employee job satisfaction at department of education Sawahlunto is high at 82,4%, (3) There is a significant correlation between organizational communication with employee job satisfaction in department of education Sawahlunto with a correlation coefficient =0,431. Keyword :organizational communications,employee job satisfaction